EFEKTIVITAS STRATEGI BRANDING ERIGO DALAM MEMBANGUN BRAND IMAGE SEBAGAI PRODUK LOKAL YANG GO INTERNATIONAL (Studi Pada Followers Instagram @erigostore) - Muhammad Arya Pratama (2023)
Branding is the process of creating and interpreting a corporate identity to convey messages, build credibility, and establish communication between products and consumers. Erigo, one of the local clothing brands, carries out a branding strategy to convey messages to the public about their identity, to build a brand image. In SMCR theory, messages such as content, structure, code, treatment and elements will affect the understanding and recipients of messages. Erigo carries out their branding strategy through the Instagram social media channel. Erigo does branding as a product that goes international, for example by issuing series from various countries in his shirt designs, and in 2021 he is carrying out the Erigo Goes to New York Fashion Week campaign. To find out how effective Erigo's branding strategy (Variable X) influences brand image as a Go-International local product (Variable Y), the testers conducted a correlation test, simple linear regression test, test the coefficient of determination, and test the hypothesis. It was found that there is a strong relationship between X and Y variables. The regression coefficient is positive. So it can be concluded that the higher the Effectiveness of Erigo's Branding Strategy, the greater its influence on Erigo's Brand Image as a Go-International Local Product. Through the test of the coefficient of determination, it was found that the effectiveness of the Erigo branding strategy had an effect of 64.1% and other factors of 35.9% outside the research.